104 Viability of Second Gamma Knife Radiosurgery vs Percutaneous Retrogasserian Balloon Compression for Primary Trigeminal Neuralgia. (August 2015) - Valerio, Jose E.; Alvarez-Pinzon, Andres M.; Coy, Sam; Sanchez Gonzalez, Marcos; Wolf, Aizik L.
Abstract : INTRODUCTION: Treatment in trigeminal neuralgia (TN) must be adapted in each patient. Surgeons must be conscious of medical, surgical, and radiation treatment modalities to suggest ideal management. Gamma knife radiosurgery (GKRS) could be used multiple times compared with percutaneous retrogasserian balloon compression for pain control. The objective of this study is evaluate the efficacy of Gamma Knife Radiosurgery and retrogasserian balloon compression in TN refractory for prior GKRS. METHODS: From retrospective chart review assessed between January 2010 and March 2013, 103 patients were selected. Patients with a diagnosis of secondary trigeminal neuralgia and/or atypical facial pain as well as patients with a history of previous vascular decompression and/or TNA blocks were excluded. Demographic characteristics, operative details, and perioperative pain treatment data were collected. Primary end points included postoperative pain relief, levels of carbamazepine, facial numbness, and complications. Continuous and categorical data were analyzed with the Wilcoxon rank sum test, Pearson's χ 2 test, or Fisher exact test, as appropriate. RESULTS: Radiosurgery and balloon compression groups contained 59 and 62 patients, respectively. Balloon compression had a lower mean postoperative pain control (36.7% vs 19%; P = .0281) and mean calculated pain control in VAS scale at 2 weeks (47.3% vs 22.65%; P = .0236), this did not translate to a statistically significant difference in mean pain control at 3 months (68.7% vs 83.93% P = .137), 18 months (57.8% vs 73.93% P = .098), and carbamazepine usage after 3 months (balloon compression [31.9%] vs GKRS [37.7%]; P = .71). Most common side effects were facial numbness postoperative v2, v3 distribution (64.23% vs 13.12%; P = .00192) and 3 months (24.68% vs 17.29%; P = .034). CONCLUSION: Balloon compression decreased acute primary trigeminal neuralgia, but did not provide a clinically substantial advantage compared with GKRS in terms of decreasing pharmacological dosage and pain relief in a 24-month period.